Item generation in the development of a questionnaire for predicting multidrug therapy compliance in leprosy - Siskawati, Yulia; Asih, Sali Rahadi; Kekalih, Aria; Menaldi, Sri Linuwih; Herqutanto, Herqutanto; Bramono, Kusmarinah (Journal of General - Procedural Dermatology and Venereology Indonesia, 2023)
Background: Lengthy therapeutic regimens in leprosy are prone to defaults, contributing to more antibiotic-resistant Mycobacterium. Intervening patients’ medical habits midway would be more complicated than understanding their perception of undergoing such regimens in advance. We study the factors considered relevant to leprosy patients’ compliance to construct a novel self-reporting questionnaire that can predict the patients’ adherence before initiating multidrug therapy. Methods: According to the Delphi methods, we conducted three rounds of interviews with twenty-three respondents from various backgrounds, including dermatologists, government officials, healthcare workers, and patients with leprosy, to infer the associated factors of the included items. Each item was scored using the Likert scale, and accepted items (scores above 75%) were classified into six-dimensional categories based on the health belief model theory. Result: The initial 236 items were simplified to 72 items. Then, a panel discussion was conducted to score each item. Finally, 48 items were accepted and categorized into 12 indicators from 6 dimensions. The 12 indicators encompass knowledge about leprosy, its severity, therapeutical options, stigma, challenges in the treatment maintenance, availability of medical facilities and workers, therapeutic impact, drug regulation, health personnel, personal beliefs, attitude, and motivation. (p Conclusion: The study identified 12 critical factors influencing adherence to leprosy treatment, contributing to the prevention of antibiotic-resistant mycobacterium and providing valuable insights through the predictive self-reporting questionnaire.